2012
DOI: 10.1038/ismej.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and metaproteomic insights into bacterial communities in leaf-cutter ant fungus gardens

Abstract: Herbivores gain access to nutrients stored in plant biomass largely by harnessing the metabolic activities of microbes. Leaf-cutter ants of the genus Atta are a hallmark example; these dominant neotropical herbivores cultivate symbiotic fungus gardens on large quantities of fresh plant forage. As the external digestive system of the ants, fungus gardens facilitate the production and sustenance of millions of workers. Using metagenomic and metaproteomic techniques, we characterize the bacterial diversity and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
138
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 47 publications
(56 reference statements)
5
138
0
Order By: Relevance
“…Future transcriptomic analyses and additional genome sequencing will likely identify more enzymes used by this fungus for biomass degradation in leaf-cutter ant fungus gardens. Previous metagenomic characterizations of bacterial communities in Atta and Acromyrmex gardens recovered mainly oligosaccharide-degrading enzymes and few CAZy families associated with the degradation of recalcitrant polysaccharides (17), suggesting that bacteria are not playing a prominent role in biomass degradation in fungus gardens. Moreover, our metaproteomic results revealed that although Ďž81,000 spectra could be confidently mapped to diverse L. gongylophorus lignocellulases, only a single spectrum could be mapped to a bacterial GH8, a CAZyme family that in bacteria is often associated with cell wall modification rather than plant biomass degradation (49).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Future transcriptomic analyses and additional genome sequencing will likely identify more enzymes used by this fungus for biomass degradation in leaf-cutter ant fungus gardens. Previous metagenomic characterizations of bacterial communities in Atta and Acromyrmex gardens recovered mainly oligosaccharide-degrading enzymes and few CAZy families associated with the degradation of recalcitrant polysaccharides (17), suggesting that bacteria are not playing a prominent role in biomass degradation in fungus gardens. Moreover, our metaproteomic results revealed that although Ďž81,000 spectra could be confidently mapped to diverse L. gongylophorus lignocellulases, only a single spectrum could be mapped to a bacterial GH8, a CAZyme family that in bacteria is often associated with cell wall modification rather than plant biomass degradation (49).…”
Section: Discussionmentioning
confidence: 95%
“…S4). Peptide matches were filtered using Sequest scores (37), MS-GF software spectral probabilities (38), and false discovery rates, as previously described (17). Moreover, all peptides with a Ďž10-ppm mass error were discarded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenylalanine production is independent of the plant material that the ants offer as fungal substrate, because 3.86 mg free and 7.33 mg protein-bound phenylalanine could be extracted per gram dry weight of L. gongylophorus grown on Potato Dextrose Agar 50 . Genes encoding enzymes for part of the aromatic amino acid biosynthesis pathway have also been discovered among Klebsiella, Enterobacter, Pantoea and Pseudomonas bacteria in A. colombica fungus gardens 51 , suggesting that bacterial symbionts may contribute phenylalanine to the symbiosis as well.…”
Section: Discussionmentioning
confidence: 99%